Mental Health Burden of the Russian-Ukrainian War 2022 (RUW-22): Anxiety and Depression Levels among Young Adults in Central Europe - Riad, Abanoub; Drobov, Anton; Krobot, Martin; Antalová, Natália; Alkasaby, Muhammad Abdullatif; Peřina, Aleš; Koščík, Michal (International journal of environmental research and public health, 2022)
Armed conflicts are public health emergencies that affect human lives at multiple levels. The mental health of adolescents and young adults is at high risk during crisis settings; therefore, this cross-sectional survey-based study aimed to evaluate anxiety and depressive symptoms among university students in the Czech Republic following the Russian-Ukrainian war of 2022 (RUW-22). The study used standardized screening instruments; the Generalized Anxiety Disorder (GAD-7) for anxiety and the Patient Health Questionnaire (PHQ-9) for depression. Of 591 students who participated in this study, 67.7% were females, 68.2% held Czech citizenship, and 63.8% were enrolled in medical or healthcare programs. The participants were highly concerned about the RUW-22 news, with a mean score of 7.17 ± 2.50 (0-10). While 34% and 40.7% of the participants in this study manifested moderate to severe levels of anxiety and depression, respectively, the mental health burden of the RUW-22 was confirmed by the positive correlation between "feeling concerned", GAD-7 (ρ = 0.454), and PHQ-9 (ρ = 0.326). Female gender, higher frequency of news following, and social media use were associated with higher levels of anxiety and depressive symptoms; thus, proposing them to be risk factors for psychological disorders following the RUW-22.
Keywords: Young Adult; Cross-Sectional Studies; students; Ukraine; Male; ozbrojené konflikty; armed conflicts; mladý dospělý; úzkostné poruchy; Adolescent; Mental Health; duševní zdraví; mužské pohlaví; deprese; Armed Conflicts; mladiství; Czech Republic; úzkost; anxiety; lidé; ženské pohlaví; Anxiety Disorders; Humans; průřezové studie; Female; Depression; patient health questionnaire; Anxiety; depression